Object-oriented programming with JavaScript - Brown, Ethan, 1975-; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2014)
"In this Object-Oriented Programming with JavaScript training course, expert author Ethan Brown will teach you how to write classically object-oriented programs in JavaScript, as well as how to take advantage of prototypal inheritance. This course is designed for users that already have experience with JavaScript. You will start by learning basic object-oriented programming concepts and JavaScript's object model, then jump into learning about scope in JavaScript. From there, Ethan will teach you about classically object-oriented JavaScript, such as object prototypes, the prototype chain, and data hiding. Finally, this training video will cover duck typing and behavior injection. Once you have completed this computer based training course, you will be fully capable of writing object-oriented programs with JavaScript. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.
Title from title screen (viewed December 18, 2014)
Date of publication taken from resource description page.
Presenter, Ethan Brown.
Keywords: JavaScript (Computer program language); Object-oriented programming languages; Electronic books